The Influence of Hedonic Pleasure, Availability of Time, and Availability of Money on Impulse Buying (Studies on The Marketplace Shopee) - Arfani, Muhammad Naufal (Terbuka Journal of Economics and Business, 2020)
The purpose of this study was to determine the effect of hedonic pleasure, time availability and availability of money on unplanned purchases at Shopee's online shopping places. The method used in this research is a questionnaire. The sample of this study amounted to 100 respondents. Statistical tests were performed using PLS-based Structural Equation Modeling. The validity test uses the loading factor value, while the reliability test uses Cronbach's alpha value, composite reliability and Average Variance Extracted (AVE). After all the results of the indicator items used in this study were valid and reliable, then the hypothesis was tested. Of the three hypotheses proposed, the first hypothesis is rejected, but the second and third hypotheses are accepted. The conclusion of this study is that hedonic pleasure has no significant effect on impulse buying, while the availability of time and availability of money have a significant effect on impulse buying in the Shopee marketplace case study.